Long term outcomes in left ventricular non-compaction. (25th November 2020) - Casas, G; Oristrell, G; Limeres, J; Gutierrez Garcia-Moreno, L; Barriales, R; Garcia-Pavia, P; Zorio, E; Gimeno, J.R; Villacorta, E; Jimenez-Jaimez, J; Ripoll, T; Bayes, A; et al.
Abstract: Background: Left ventricular non-compaction (LVNC) is a highly heterogeneous entity with a wide phenotypic expression. Risk factors have not been well established and prognostic stratification remains challenging. Objectives: Describe long term outcomes of LVNC patients and determine predictors of cardiovascular events. Methods: Prospective multicentric study of consecutive patients fulfilling imaging criteria for LVNC. Demographic, ECG, imaging and genetic variables were collected. End points were heart failure (HF), ventricular arrhythmias (VA), systemic embolisms (SE) and all-cause death. Major adverse cardiovascular event (MACE) was described as the combination of the four previous end points. Results: 592 patients from 13 referral centres were included from 2000 to 2018. Mean age at diagnosis was 45 years, 252 (43%) were female and mean LVEF was 48% (Table 1). During a median follow-up of 55 months (IQR 24–90), 144 (25%) patients presented HF, 101 (18%) VA, 27 (5%) SE and 33 (6%) died. MACE occurred in 223 (39%) patients. In multivariate analysis, independent predictors of HF were LVEF (OR 0.9), PSAP (OR 1.17) and late gadolinium enhancement (LGE) (OR 1.3). VA were independently associated with LVEF (OR 0.97) and LGE (OR 2.51). Independent predictors of SE were LVEF (OR 0.96) and LA diameter (OR 1.07). No independent predictors of all-cause death could be described. MACE were independently associated with LVEF (OR 1.04) and PSAP (OR 1.08) (Table 1). Among patients who underwent genetic testing (340, 57%), genotype was associated with outcomes: MYH7 and ACTC1 variants were protective while multiple mutations, TTN and MYBPC3 variants exhibited worse prognosis. Conclusions: In a large prospective multicentric cohort of LVNC patients, there was a moderate long term incidence of cardiovascular events. LVEF and fibrosis were the main predictors and genotype was a modifier of outcomes. These factors might be used to risk stratify LVNC patients. Funding Acknowledgement: Type of funding source: None